Two Fish in a Pod. Mislabelling on Board Threatens Sustainability in Mixed Fisheries - Blanco-Fernandez, Carmen; Erzini, Karim; Rodriguez-Diego, Sara; Alba-Gonzalez, Pablo; Thiam, Ndiaga; Sow, Fambaye Ngom; Diallo, Mamadou; Viðarsson, Jónas R.; Fernández-Vidal, Duarte; Gonçalves, Jorge M. S.; Rangel, Mafalda; Stobberup, Kim; et al. (Frontiers in Marine Science, 2022)
Accuracy in reporting captures is a key element to achieve fisheries sustainability. However, identification of the catches might be a challenge when two or more species are morphologically similar and caught jointly, like the mixed fisheries of black hakes in East Atlantic African waters. Black hakes (Merluccius senegalensis and M. polli) are tough to differentiate without previous training due to their high morphological resemblance. The two species are managed as a single stock, although the biological differences between them suggest the need of a separate management. In this study, a total of 806 black hakes were visually identified by fishers on deck of fishing vessels operating in Mauritania and Senegal waters, then assigned to a species by sequencing 450bp of the Mitochondrial Control Region. Comparing the results with visual identification we found 31.4% of the total catch were incorrectly labelled on board by the fishermen. The accuracy of the fishers’ identification depended on the depth of capture and on fish size, larger individuals caught from deeper waters being more correctly assigned to M. polli. Mislabelling biased to M. polli suggests that M. senegalensis, already catalogued as endangered, is being underreported, which could endanger the conservation of this species and threaten the sustainability of black hake fisheries. Our results highlight the need for separate evaluation of the stocks in mixed fisheries for morphologically similar fish. Thus, monitoring through DNA barcoding in the very first step of the seafood chain surveys would improve accurate species delimitation and reduce its impact on the correct assessment of the stocks.